2020
DOI: 10.1002/vms3.353
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prostaglandin and gonadotrophins (GnRH and hCG) injection combined with the ram effect on progesterone concentrations and reproductive performance of Karakul ewes during the non‐breeding season

Abstract: The effect of prostaglandin and gonadotrophins (GnRH and hCG) combined with the ram effect on the progesterone (P4) concentrations and reproductive performance of Karakul ewes was investigated during non‐breeding season. Ewes (n = 93) received a male effect and were divided into two treatment groups including GnRH ‐ hCG (hCG, n = 32), GnRH ‐ GnRH (GnRH, n = 30) and a control (n = 31) group. This study was carried out from April (hormonal injection) to October (lambing). The first doses of GnRH (4.2 μg, Buserel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Follicular growth and subsequently oestrous signs in hMG‐treated ewe may be due to its FSH‐ and LH‐like actions (Hussein et al., 2021). In the present study, some control ewes got pregnant but the number was significantly lower than that of the treatment groups because the ram effect may be associated with ovulation in some ewes during the non‐breeding season (Ayaseh et al., 2021; Dehkordi et al., 2022). In addition, the ram effect is able to induce silent ovulation or short cycles in control group.…”
Section: Discussionmentioning
confidence: 50%
“…Follicular growth and subsequently oestrous signs in hMG‐treated ewe may be due to its FSH‐ and LH‐like actions (Hussein et al., 2021). In the present study, some control ewes got pregnant but the number was significantly lower than that of the treatment groups because the ram effect may be associated with ovulation in some ewes during the non‐breeding season (Ayaseh et al., 2021; Dehkordi et al., 2022). In addition, the ram effect is able to induce silent ovulation or short cycles in control group.…”
Section: Discussionmentioning
confidence: 50%
“…However, the formation of corpus luteum in response to single or multiples injections of GnRH was not reported by Jordan and colleagues in seasonal anestrus ewes (Jordan et al, 2009). This is because follicle atresia might also occur if responsive follicles are not present when GnRH is given to animals (Twagiramungu et al, 1995), which complete avoids the possibility of corpus luteum formation (Ayaseh et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…In oestrus‐synchronized Awassi ewes after short‐term progestagen administration, a dose of 50 μg GnRH (Gonodarelin diacetate) given 48 h after removal of the progestagen pessary decreased the pregnancy rate to 37.9% compared with 55.2% in its own control group (Kutlu & Dinç, 2021). Some other studies, in which injection of a single dose of GnRH (24 h ‐ 48 h after removal of the progestagen pessary/on the day of oestrus) was performed during the breeding season, reported varying degrees of positive responses from 4% to 73.2% in pregnancy rate (Kutlu & Dinç, 2021; Sirjani et al, 2012; Walker et al, 1989), while some others have reported no changes (Ayaseh et al, 2021; Cavalcanti et al, 2012; Olivera‐Muzante et al, 2011; Türk et al, 2008) or decrease in pregnancy rate (Olivera‐Muzante et al, 2013). Moreover, Biehl et al (2017) reported that the use of GnRH was efficient to increase the pregnancy rate in Santa Ines ewes undergoing the fixed time artificial insemination procedure, and the best protocol to GnRH administration was at the time of insemination because only three managements were required.…”
Section: Discussionmentioning
confidence: 99%
“…Although GnRH is already widely used in ovine fixed time artificial insemination programmes (Hameed et al, 2021), the effects of GnRH on pregnancy rates are controversial (Menchaca & Rubianes, 2004). Some studies reported that a single dose of GnRH given 24 to 48 h after pessary removal increased the pregnancy rate (Biehl et al, 2017; Kutlu & Dinç, 2021), while some others have reported no changes (Ayaseh et al, 2021; Cavalcanti et al, 2012; Olivera‐Muzante et al, 2011; Reyna et al, 2007; Türk et al, 2008) or even decreased the pregnancy rate (Martemucci & D'Alessandro, 2011; Olivera‐Muzante et al, 2013; Walker et al, 1989).…”
Section: Introductionmentioning
confidence: 99%